WT1 peptide-based immunotherapy for refractory thymic epithelial malignancies - Suzuki, Mikito; Hishida, Tomoyuki; Asakura, Keisuke; Asamura, Hisao (Mediastinum; Vol 3 (April 2019): Mediastinum, 2019)
Thymic epithelial tumors (TETs), including thymomas, thymic carcinomas, and thymic neuroendocrine tumors, are rare malignant tumors arising in the thymus. For resectable disease, the recommended treatment is surgical resection. On the other hand, TETs are often diagnosed in advanced form. If resection is deemed to be difficult, systemic chemotherapy with or without radiotherapy is administered. For thymomas, platinum- and anthracycline-based regimens including ADOC (cisplatin, doxorubicin, vincristine, and cyclophosphamide) and non-anthracycline regimens such as cisplatin/etoposide, carboplatin/paclitaxel, and carboplatin/amrubicin have been used as first-line regimens with a reported response rate of 35–56% (1,2).